Impact Assessment of Digital Learning Tools in South African Higher Education - Esan, Dorcas Oladayo; Masombuka, Themba (Journal of Information System and Informatics, 2025)
Technological advancements have significantly reshaped the operational landscape of tertiary institutions, enhancing both student and academic efficiency processes. In South Africa, many students in higher learning institutions scrambled to use technology for teaching and learning due to load shedding, poor internet connectivity, lack of technological skills, lack of technology training by the tertiary institutions, etc. This study employs the UTAUT to understand better how technological innovations impact South African higher institutions. The UTAUT model includes components such as effort expectancy, self-awareness, social influence, facilitating conditions, and voluntary use to fully understand the factors influencing technology development and adoption. Three hundred and ten (N=310) students from underprivileged tertiary institutions in the Eastern Cape participated in this study. The study used a quantitative research methodology based on a 5-point Likert scale to gauge the respondents' intention to use technology for teaching and learning. Regression analysis and NOVA statistical tools were used to analyse the acquired data. The findings revealed that most participating students believe that technological advancements had a positive impact on their ability to teach and learn. The research findings imply that faculty should implement training programs on digital tools, improve IT infrastructure, provision of free internet bundles, and develop policies that support the adoption of e-learning technologies.